516 views
2 votes
The work of a student to solve the equation 2(3x − 4) = 8 + 2x + 4 is shown below: Step 1: 2(3x − 4) = 8 + 2x + 4 Step 2: 5x − 6 = 12 + 2x Step 3: 5x − 2x = 12 + 6 Step 4: 3x = 18 Step 5: x = 6 In which step did the student first make an error and what is the correct step? (5 points) Step 2; 6x − 6 = 2(6 + x + 2) Step 2; 6x − 8 = 12 + 2x Step 3; 5x − 2x = 12 − 6 Step 3; 5x + 2x = 12 + 6

User TFischer
by
6.1k points

2 Answers

7 votes

Answer:

b

Explanation:

User Tylerthemiler
by
5.7k points
4 votes

Answer:

B: Step 2; 6x − 8 = 12 + 2x

Explanation:

the student added 2 x 4 during the distributive property but you must multiply so you get 8 rather than 6.

User Dsetton
by
5.4k points